Аналізування ризиків, що виникають при залученні нових збутових каналів у процесі диверсифікації маркетингової діяльності малих машинобудівних підприємств - Шпак, Н. О.; Кирилич, Т. Ю. (Видавництво Львівської політехніки, 2014)
Проаналізовано ризики, що виникають у разі залучення нових збутових каналів процесі під час диверсифікації маркетингової діяльності малих машинобудівних підприємств; згруповано їх за сферами виникнення; встановлено, що забезпечення захисту від декількох категорій ризиків, які виявлені під час дослідження, дасть змогу досягти високого показника мінімізації усіх категорій ризиків; запропоновано потенційні шляхи мінімізації або усунення виокремлених груп ризиків. The paper clarifies that taking a positive management decision to diversify marketing activity in the context of its key element (sales) is influenced by plenty of risks. Taking into account the above mentioned, risks appearing in attracting new sale channels in marketing activity diversification have been analyzed; they have been grouped together according to areas of their appearing. The level of the risks importance and probability of taking place have been estimated. It was found that ensuring the protection against several risk types revealed in the study will allow us to achieve a high level of minimization of all risk types; the potential ways of minimization or elimination of risk groups have been proposed. The methods of decreasing probability of the fact that the risk will take place and risk prevention methods are analyzed in order to exclude risk negative impact in diversification of the marketing activity of small machine-building enterprise. The way of application of the “sum” method as one of the types of ABC –analyses is studied to distinguish the biggest threats during distributing channels diversification for small machine-building enterprise.
Analysis of risks appearing in attracting new sale channels in marketing activity diversification of small industrial enterprises
Keywords: ризик; маркетингова діяльність; диверсифікація; АВС-аналіз; канал розподілу; мале машинобудівне підприємство; risk; marketing activity; diversification; ABC-analysis; sale channel; small industrial enterprise